Guidelines of the First International Consensus Conference on Endovenous Thermal Ablation for Varicose Vein Disease – ETAV Consensus Meeting 2012. (May 2015) - Pavlović, Miloš D; Schuller-Petrović, Sanja; Pichot, Olivier; Rabe, Eberhard; Maurins, Uldis; Morrison, Nick; Pannier, Felizitas
Aim: Endovenous thermal ablation (ETA) procedures are catheter-directed, ultrasound (US)-guided thermal methods for treatment in varicose veins disease. Radiofrequency, laser or steam energy thermally denatures vein wall collagen, leading first to vein wall inflammation, then fibrosis and finally to occlusion. The aim of this guideline is to give evidence-based recommendations for ETA procedures. Methods: These guidelines were drafted during a consensus meeting of a group of experts in the field of ETA in June 2012 (Hvar, Croatia) under the auspices of the International Union of Phlebology (IUP). These guidelines review the present state of knowledge as reflected in peer-reviewed published medical literature. The recommendations of these guidelines are graded according to the American College of Chest Physicians Task Force recommendations on Grading Strength of Recommendations and Quality of Evidence in Clinical Guidelines. Results: Recommendations on the use of ETA procedures were made based on the quality of evidence for efficacy, safety, tolerability, cosmetic outcome, patient satisfaction/preference and, where appropriate, on the experts' opinion. Health economics were not considered, since differences in national health systems and pricing make it difficult to form general conclusions that are relevant at an international level.